Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1038/s41467-020-17893-z
|View full text |Cite
|
Sign up to set email alerts
|

American mastodon mitochondrial genomes suggest multiple dispersal events in response to Pleistocene climate oscillations

Abstract: Pleistocene glacial-interglacial cycles are correlated with dramatic temperature oscillations. Examining how species responded to these natural fluctuations can provide valuable insights into the impacts of present-day anthropogenic climate change. Here we present a phylogeographic study of the extinct American mastodon (Mammut americanum), based on 35 complete mitochondrial genomes. These data reveal the presence of multiple lineages within this species, including two distinct clades from eastern Beringia. Ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 65 publications
(90 reference statements)
1
13
0
Order By: Relevance
“…The 3 African elephant composite melt profiles -P3, P8, and P9, were unique to African elephants, and the sequences of the 16S and Cytb melt peaks comprising those composite melt profiles were specific to African elephants. Although no mastodon sequence information was obtained in this study, we observed 1 mastodon-specific composite melt profile, P10, which consisted of 16S and Cytb melt peak sequences that were unique to American mastodon [20] in this study of limited sample size. Since Pacific mastodon was also observed to have a P10 composite melt profile, we can infer that the 16S and Cytb melt peak sequences of Pacific mastodon would likely be the same as they are for American mastodon, although further investigation is required to be certain.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…The 3 African elephant composite melt profiles -P3, P8, and P9, were unique to African elephants, and the sequences of the 16S and Cytb melt peaks comprising those composite melt profiles were specific to African elephants. Although no mastodon sequence information was obtained in this study, we observed 1 mastodon-specific composite melt profile, P10, which consisted of 16S and Cytb melt peak sequences that were unique to American mastodon [20] in this study of limited sample size. Since Pacific mastodon was also observed to have a P10 composite melt profile, we can infer that the 16S and Cytb melt peak sequences of Pacific mastodon would likely be the same as they are for American mastodon, although further investigation is required to be certain.…”
Section: Discussionmentioning
confidence: 64%
“…Each composite melt profile, its corresponding melt peaks, and the relevant SNPs are presented in Table 4. Since the mastodon samples that yielded complete composite melt profiles (3 Pacific mastodon samples, and 1 American mastodon sample) failed to produce sequencing results at 16S and Cytb, mastodon sequence analysis relied on whole mitochondrial genome sequences of American mastodon [20]. All sequences produced by this study (N = 1062) were deposited in GenBank (https://www.ncbi.nlm.nih.…”
Section: Sanger Sequencing Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other animals underwent sometimesextensive range shifts (caribou and muskox no longer live in the southeastern United States, as each had in the Pleistocene), changes in abundance, and extirpation (14,24,28,29). Ancient DNA evidence shows there were population bottlenecks and declining genetic diversity in the Late Pleistocene among a number of extant and extinct taxa, in some instances, beginning well before the first appearance of humans in North America (30)(31)(32)(33)(34)(35).…”
Section: Why Humans Aren't To Blamementioning
confidence: 99%
“…Building a case Calculated adjusted residuals are in parentheses, significant values are in bold (data from Table 2). χ 2 = 6.659, df = 2, P = 0.036. will require high-resolution chronologies and ancient DNA evidence to determine when each species began its downward demographic spiral, and track its population dynamics and range through to its extinction (7,13,31,34,35). It will also require detailed, region-specific records of the pace and magnitude of tclimate change, and of changes in the species and structure of the biotic community (drawn from pollen, macrofossils, ancient environmental DNA, and other proxies) (24,28,49,64,65,67,68,99).…”
Section: Getting Past the Impassementioning
confidence: 99%